The Castle Slaves of the Gambia River : A Creole Community in the Eighteenth Century Atlantic World - Tuck, Michael W., (African History ;, 2026)
The Castle Slaves of the Gambia River is the first history of a community of enslaved Africans in eighteenth-century West Africa. It provides a vivid portrait of the people whose labor sustained Atlantic trade-such as Hector, a skilled carpenter. Despite hardships they showed remarkable resilience, forging families and communities amid illness and loss, as seen in the tragic fate of Serva. Yet their story is not only one of suffering. The daring escape of Injee and Dukane is evidence of their resistance. Together, their lives reveal the crucial role they played in shaping a distinct creole cultural world along the West African coast.